Serotonergic psychedelics for depression: What do we know about neurobiological mechanisms of action? - Husain, Muhammad Ishrat; Ledwos, Nicole; Fellows, Elise; Baer, Jenna; Rosenblat, Joshua D.; Blumberger, Daniel M.; Mulsant, Benoit H.; Castle, David J. (Frontiers in Psychiatry, 2023)
Introduction: Current treatment options for major depressive disorder (MDD) have limited efficacy and are associated with adverse effects. Recent studies investigating the antidepressant effect of serotonergic psychedelics – also known as classic psychedelics - have promising preliminary results with large effect sizes. In this context, we conducted a review of the putative neurobiological underpinnings of the mechanism of antidepressant action of these drugs. Methods: A narrative review was conducted using PubMed to identify published articles evaluating the antidepressant mechanism of action of serotonergic psychedelics. Results: Serotonergic psychedelics have serotonin (5HT)2A agonist or partial agonist effects. Their rapid antidepressant effects may be mediated – in part - by their potent 5HT2A agonism, leading to rapid receptor downregulation. In addition, these psychedelics impact brain derived neurotrophic factor and immunomodulatory responses, both of which may play a role in their antidepressant effect. Several neuroimaging and neurophysiology studies evaluating mechanistic change from a network perspective can help us to further understand their mechanism of action. Some, but not all, data suggest that psychedelics may exert their effects, in part, by disrupting the activity of the default mode network, which is involved in both introspection and self-referential thinking and is over-active in MDD. Conclusion: The mechanisms of action underlying the antidepressant effect of serotonergic psychedelics remains an active area of research. Several competing theories are being evaluated and more research is needed to determine which ones are supported by the most robust evidence.